2010
DOI: 10.1007/s10695-010-9442-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the composition and importance of free amino acids in semen of gilthead sea bream, Sparus aurata, and perch, Perca fluviatilis

Abstract: A comparative study was conducted on the free amino acid composition of gilthead sea bream, Sparus aurata, and perch, Perca fluviatilis. Also the effect of 21 free amino acids on sperm motility was investigated. Spermatozoa were incubated in species-specific motility-inhibiting saline solution containing the different amino acids for 48 h. Thereafter, the motility was activated and investigated using computer-assisted cell motility analysis. Twelve free amino acids, respectively, were detected in S. aurata and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Amino acids are also oxidisable substrates for sperm and can bind toxic heavy metals, thus preserving the viability of spermatozoa (Chaudhury, Sharma, Jagannathan, & Guha, ; Papp, Gróf, & Menyhárt, ; Patel, Srivastava, Phadke, & Govil, ). Lahnsteiner () reported that valine has positive effect on sperm motility in Perca fluviatilis . Our experiment confirmed that deficiency of valine in seminal plasma may contribute to the poor sperm motility of asthenozoospermic men.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids are also oxidisable substrates for sperm and can bind toxic heavy metals, thus preserving the viability of spermatozoa (Chaudhury, Sharma, Jagannathan, & Guha, ; Papp, Gróf, & Menyhárt, ; Patel, Srivastava, Phadke, & Govil, ). Lahnsteiner () reported that valine has positive effect on sperm motility in Perca fluviatilis . Our experiment confirmed that deficiency of valine in seminal plasma may contribute to the poor sperm motility of asthenozoospermic men.…”
Section: Discussionmentioning
confidence: 99%
“…Lysine, threonine, tryptophan, and valine are essential amino acids, and their levels in plasma were seriously affected by food intake. Good sources of these amino acids are high-protein foods such as animal products [ 48 , 49 ]. Hydroxyproline is a non-proteinogenic amino acid, which is produced by the hydroxylation of proline.…”
Section: Discussionmentioning
confidence: 99%
“…Arginine was the main free amino acid in the spermatozoa of Oncorhynchus mykis s, Cyprinus carpio and Perca fluviatilis . In addition, arginine, glutamic acid and methionine were found in the semen of several fish species where sperm motility was improved when spermatozoa were co-incubated with methionine [ 3 , 4 ]. In mouse, cysteine analogs can increase the fertilization of frozen-thawed sperms [ 5 ].…”
Section: Introductionmentioning
confidence: 99%